The presence of a fat layer after neoadjuvant chemotherapy as an indicator of prognosis in osteosarcoma - Huang, Junqi; Xie, Zengru (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to evaluate the potential of magnetic resonance imaging (MRI) to monitor the response in patients with osteosarcoma receiving chemotherapy and to assess the correlation between the presence of a fat layer surrounding the tumor after neoadjuvant chemotherapy and prognosis.MethodsIn total, 28 patients with osteosarcoma were included in this retrospective study. All patients underwent chemotherapy and surgery. MRI scans of the patients were evaluated before and after neoadjuvant chemotherapy. The prognostic factors included histological response and alkaline phosphatase (ALP) level. Relapse and survival at follow-up were defined as patient outcomes. The log-rank test was used to compare these factors with various MRI characteristics (e.g. change in maximum lesion length before and after chemotherapy, change in maximum edema, and fat layer presence after chemotherapy).ResultsThe median time of follow-up was 64.3 ± 41.5 months. The 3- and 5-year event-free survival rates were 75.0% and 67.9%, respectively. ALP levels after chemotherapy were associated with tumor necrosis (p = 0.01). Change in maximum lesion length [p = 0.044; odds ratio (OR) = 0.035; confidence interval (CI): 0.01–0.911] was a predictor of survival. Changes in edema on T2-weighted sequences (p = 0.979; OR = 0.989, CI: 0.437–2.242) were not significant. The presence of a fat layer (p = 0.013; OR = 0.000; confidence CI: 0.000–0.018) predicted good event-free survival.ConclusionsThe presence of a fat layer correlated with good prognosis in patients with osteosarcoma. MRI characteristics in the early stages could help to inform decision-making about treatment strategy.